Kollegialitet, terapi och medling: expertgranskning i psykiatrimål (Sociologisk Forskning, 2002)
Collegealism, therapy and mediation - experts’ interpretative repertoires in court hearings relating to compulsory psychiatric careThis article investigates the role of court appointed psychiatrists (AP) in Swedish court hearings relating to compulsory psychiatric care. Data consists of tape recordings and documents from twelve court hearings together with informal interviews with actors in court. The discourse in court is analyzed in terms of interpretative repertoires. The possibility for APs to examine each case is limited by shortage of time and resources. Furthermore, APs may have to take into account an out-of-court, professional relationship to the treating psychiatrist(CP). We find that conversation between APs and CPs frequently are carried out in a collegiate repertoire. These circumstances inhibit a detailed critical examination of the CP’s application for compulsory care, which in turn helps explaining why APs seldom assess cases different from CPs. How, then, is the AP’s status as expert reproduced in courtroom conversation? This is accomplished by using a disclosing repertoire, which invites the patient to produce incoherent talk. Expert status is also reproduced when APs give medical advise to patients in a therapeutic repertoire. Applying a mediating repertoire, APs attempt to resolve clinical conflicts between CPs and patients. As a result, the legal conflict at stake is downplayed.